2015
DOI: 10.24014/ja.v5i2.1349
|View full text |Cite
|
Sign up to set email alerts
|

Dampak Perkebunan Kelapa Sawit Terhadap Perekonomian Wilayah Di Kabupaten Rokan Hulu

Abstract: This research aims to know (1)  labor absorption of oil palm farmers; and (2) the productivity of oil palm farmers, (3) farmer perception, and (4) the palm plantation contribution to the regional income. The research was conducted in September 2013 until November 2013. Location of research in sub-districts of North Tambusai, Kunto Darussalam, Tandun, and Kabun in Rokan Hulu District. The method used interviews, questionnaires, and documentation. Sampling was done by purposive. Results of this research is the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
14

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 1 publication
0
7
0
14
Order By: Relevance
“…All respondents explained that the palm oil industry waste occurs every week and it accumulates into waste heap found in many spots. Siradjuddin [18] in his research also confirmed that the waste produced from palm oil processing will have some negative impacts on the environment such as the quantity and quality of natural resources, and the environment.…”
Section: Society's Response To Industrial Waste From Palm Oil Processingmentioning
confidence: 84%
“…All respondents explained that the palm oil industry waste occurs every week and it accumulates into waste heap found in many spots. Siradjuddin [18] in his research also confirmed that the waste produced from palm oil processing will have some negative impacts on the environment such as the quantity and quality of natural resources, and the environment.…”
Section: Society's Response To Industrial Waste From Palm Oil Processingmentioning
confidence: 84%
“…Endokaprium merupakan tempurung berwarna hitam dan keras. Endosperm atau disebut juga kernel merupakan penghasil inti sawit, sedangkan lembaga atau embrio merupakan bakal tanaman (Siradjuddin, 2015).…”
Section: )unclassified
“…Kurangnya modal di kalangan petani rakyat menjadi maklum apabila melihat skala prioritas petani kelapa sawit rakyat dalam menggunakan hasil dari usaha tani kelapa sawitnya adalah untuk biaya hidup, pendidikan anak, perluasan dan pendirian rumah, serta perluasan kebun kelapa sawit/ekstensifikasi (Siradjuddin 2015). Penelitian tersebut juga dikuatkan oleh penelitian dari Husin (2012) yang menyebutkan bahwa hasil dari usaha tani petani kelapa sawit rakyat di Sumatra Selatan diprioritaskan untuk konsumsi, pendidikan, dan kesehatan.…”
Section: Pola Swadayaunclassified